A Comparison Review of Kevin Lynch's Urban Theory with the Chinese Cosmography of Feng Shui in the Heritage Area, Case Study: Pasar Baru, Jakarta. Issue 1 (November 2021) - Meliana, S; Rombe, O SC; Henry, L; Fajarwati, A AS; Rachmayanti, I
Abstract: Jakarta is facing the reality of becoming one of the megacities in the world. As a megacity, Jakarta will continue to face critical problems, including environmental issues that occur not only in Jakarta but also in the surrounding areas. The research area is Pasar Baru, the oldest shopping area in Central Jakarta established in 1820. Naturally, this area should have a high historical value for the development of the City of Jakarta. This study explored the "shopping arcade" corridor from Kevin Lynch's urban theory of "The Image of The City" to strengthen the implementation of re-planning the Pasar Baru in the future. This study aims to find how the view of The Image of The City can support the idea of re-planning the Pasar Baru from a tangible point of view, physically visible, and an intangible point of view through the spiritual approach of Feng Shui cosmography. The research uses qualitative methods supported by collecting data in literature reviews, surveys and analyzing them. The study found that the concept given by Kevin Lynch can help decision-makers of a city to be more responsible in making policies in designing a sustainable city to carry out conservation actions, not only political goals.